BAP1 is a haploinsufficient tumor suppressor linking chronic pancreatitis to pancreatic cancer in mice - Stephanie Perkail (Nature Portfolio, 2020)
Chronic pancreatitis is linked with an increased risk of pancreatic cancer. Here the authors show that genomic instability due to the loss of BRCA1 associated protein-1, frequently observed in patients with pancreatic cancer, is associated with chronic pancreatitis and predisposes to cancer development.